Excellent Service: Competence Of Officers According to Islamic Ethics - M. Fauzi (Universitas Darussalam Gontor, 2023)
Excellent service is the best service that has met the service criteria set by the company. One of the components in providing excellent service is the competence of service providers. Officer competence consists of officer attitude, officer discipline, officer accuracy, officer responsibility, and officer knowledge in service. This research is a field research using a qualitative approach. This study obtained the results that the competence of service providers has an important role in creating customer satisfaction. Viewed from the perspective of Islamic ethics, it is in harmony with Islamic ethics, where science and ethics/adab have high nobility.